The Role of Organizational Culture in Employee Retention in Kosovar Businesses - Sylejmani, Mimoza; Mesko, Maja (Journal of Organizational Psychology, 2024)
This research aimed to examine the impact of organizational culture on employee retention, providing insights to enhance long-term engagement and satisfaction. A mixed-methods approach was used, beginning with a comprehensive literature review of organizational culture and employee retention. Surveys were conducted with a representative sample of employees across different sectors in Kosovo. The data were analyzed using regression and correlation techniques to identify quantitative relationships between organizational culture and retention. The findings reveal that organizational culture plays a significant role in employee retention. Specifically, cultures focused on employee well-being, career development, and transparency are positively associated with higher retention rates. Employees are more likely to stay with organizations that align with their values, offer support, and create a transparent working environment. Conversely, toxic cultures marked by negativity and poor leadership are linked to higher turnover. The study underscores the importance of fostering a positive, inclusive culture that prioritizes employee growth. Kosovar businesses should invest in employee development, training, and continuous feedback to build a productive environment that supports retention.